2021
DOI: 10.1002/hyp.14380
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary estimate of how stream water age is influenced by changing runoff sources in the Nagqu river water shed, Qinghai‐Tibet Plateau

Abstract: Stream water age is an essential indicator of stream water renewal and pollutant transport rates. Recently, the concept of young water fractions, calculated using stable isotopic data, was proposed as a measure of stream water age. However, the current calculation methods do not classify stream water fractions with annual cycles (365 days), which are helpful to understand the sources of runoff and the water renewal rate in the watershed. In this study, we took the Nagqu River Watershed (NRW, with an area of 16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 66 publications
0
8
1
Order By: Relevance
“…Although a distinctly positive correlation between streamflow and groundwater F yw has been observed in temperate regions (Yang et al, 2021), no consistent relationship was found between streamflow and SPG F yw and elevation in this study. This is because the influence of temperature, particularly at elevations >5,000 m (Song et al, 2017), far outweighs the effects of elevation changes.…”
Section: Control Of Water Age By Underlying Surface Landscapecontrasting
confidence: 91%
See 1 more Smart Citation
“…Although a distinctly positive correlation between streamflow and groundwater F yw has been observed in temperate regions (Yang et al, 2021), no consistent relationship was found between streamflow and SPG F yw and elevation in this study. This is because the influence of temperature, particularly at elevations >5,000 m (Song et al, 2017), far outweighs the effects of elevation changes.…”
Section: Control Of Water Age By Underlying Surface Landscapecontrasting
confidence: 91%
“…In a previous study, the water age was calculated for 254 streams worldwide, revealing an average F yw of 0.26, with 89% > 0.05 (Jasechko et al, 2016). Recent studies calculated the F yw of streamflow for several small basins with permafrost, resulting in values of 0.151 (Song et al, 2017), 0.23 (Yang et al, 2021), 0.3 (S.…”
Section: Control Of Water Age By Permafrostmentioning
confidence: 99%
“…The last group of papers exemplify the diversity of approaches that are available to assess water ages under different climates and using different type of tracers. The hydrological systems investigated in this group include: an agricultural catchment in France (Benettin et al, 2020), the aquifer of a forested catchment in Sweden (Kolbe et al, 2020), two sites in the tropics, where one is a hillslope of volcanic ash soil (Mosquera et al, 2020) and the other is a rainforest catchment (Correa et al, 2020) and two sites in China, where one is a Karst catchment (Zhang et al, 2020) and the other is a large, high-elevation river basin (Yang et al, 2021). Water age is used by Benettin et al (2020) to explain catchment-scale removal of agricultural nitrate.…”
Section: Miscellaneous Papersmentioning
confidence: 99%
“…Because of this connectivity, young water was estimated to contribute almost entirely to streamflow right after a storm event, with implications for the quick transport of contaminants. Finally, Yang et al (2021) worked on three sub-basins of about 5000 km 2 each and identified the need for age indicators that quantify not just the fraction of young water but also the fractions of water younger/ older than 1 year. They proposed a preliminary methodology based on the annual water balance to compute such fractions and found that on average the fraction of water younger than 1 year, and thus affected by just 1 cycle of thawing/freezing, was about 80%.…”
Section: Miscellaneous Papersmentioning
confidence: 99%
“…Therefore, the influence of permafrost changes, climatic factors, and vegetation variations on catchment MRT in a high-altitude permafrost catchment is rarely evaluated. For instance, Song et al (2017) and Yang et al (2021) have investigated water age in permafrost catchments in the hinterland of the Tibetan Plateau (TP) and explored the influence of vegetation and climatic factors on water age. The effects of permafrost freeze-thaw cycles on water MRT in Arctic permafrost catchments have also been reported (Tetzlaff et al, 2018).…”
Section: Introductionmentioning
confidence: 99%